Strategic hospital health promotion on patient satisfaction through healthcare services quality - Siregar, Novalina; Girsang, Ermi; Wau, Herberd (Institute of Computer Science (IOCS), 2024)
Patient satisfaction is when hospital services meet patients' needs, desires, or expectations. The government must promote everyone's right to health information and education, especially in hospitals, and guarantee comprehensive health services based on Minister of Health Regulation Number 004 of 2012 for optimal, effective, efficient, integrated, and sustainable hospital health services. The study was carried out using quantitative methods. Primary data was collected through questionnaires from patients at Royal Prima Medan Hospital, and 180 samples were obtained. Data was processed using SEM-PLS. The research results show that all hypotheses are accepted, and all variables have a positive and significant effect. The research results prove that implementing hospital health promotion helps improve the quality of health services (t-statistic value 7.294) and increase patient satisfaction (t-statistic value 4.419). Patients will be more loyal if their expectations are met from the health promotion carried out and the quality of service they perceive (t-statistic value 2.142). So, it can be concluded that government policy is appropriate in providing direction for hospitals to promote hospital health. Patients expect hospitals to have good service quality, cleanliness, and comfortable health facilities for patient satisfaction. Patients will be more loyal if their expectations are met, based on the perception of service quality and promotions carried out by the hospital, through the quality of personnel, and the empowerment of the community around the hospital.